Indications of caesarean section in pregnant women attending a public maternity teaching hospital and private hospitals in Sulaimani city Iraq - Sara Omar Hassan; Shelan Qahraman Shakor; Rozhan Yassin Khalil; Salar Ibrahim Ali (Journal of the Pakistan Medical Association, 2023)
Objective: To determine the frequency and indications of caesarean sections among pregnant women in an urban setting. Method: The cross-sectional study was conducted from October 1, 2021, to February 1, 2022, at public-sector Maternity Teaching Hospital and private-sector Baxshin and Harem hospitals in Sulaimani, Iraq, after approval from the ethics review committee of the College of Health and Medical Technology, Sulaimani. The sample comprised pregnant women who were admitted to the maternity wards and who underwent caesarean section. Data was collected using a predesigned questionnaire filled through face-to-face interviews individually. Data was analysed using SPSS 25. Results: There were 474 pregnant women with mean age 28±6.87 years. Of the total, elective caesarean section cases were 384(81%) and emergency cases were 90(19%). The main indications of caesarean section were mother’s request 266(56.2%), fear of pain in natural vaginal delivery 375(79.1%), history of previous caesarean section 38(8%), cephalopelvic disproportion 26(5.5%), history of diabetes 21(4.4%), pre-eclampsia 19(4%) and bad obstetric history/infertility 10(2.1%). Age, parity, previous history of caesarean section and mother’s occupation were significantly associated with the type of caesarean section (p<0.05). Conclusion: Caesarean section rates were found to be much higher than recommended. Keywords: Prevalence, Caesarean section, Indications, Suliamani city, Iraq.